An efficient procedure for the recovery of DNA from formalin-fixed paraffin-embedded tissue sections. Issue 1 (26th July 2022) - Oba, Utako; Kohashi, Kenichi; Sangatsuda, Yuhei; Oda, Yoshinao; Sonoda, Koh-Hei; Ohga, Shouichi; Yoshimoto, Koji; Arai, Yasuhito; Yachida, Shinichi; Shibata, Tatsuhiro; Ito, Takashi; Miura, Fumihito
Abstract: With the advent of new molecular diagnostic techniques, retrieving DNA from the formalin-fixed paraffin-embedded (FFPE) tissues has become an essential yet challenging step for efficient downstream processes. Owing to low quality and quantity of DNA retrieved from the FFPE sections, the process is often impractical and needs significant improvements. Here, we established an efficient method for the purification of DNA from FFPE specimens by optimizing incubation temperature, incubation time, and the concentration of a formalin scavenger tris(hydroxymethyl)aminomethane (Tris) for reverse-crosslinking. The optimized method, named "Hi ghly concentrated T ris-mediated DNA e xtraction" (HiTE), yielded three times the DNA yield per tissue slice compared with a representative DNA extraction kit. Moreover, the use of HiTE-extracted DNA increased the yield of the sequencing library three times and accordingly yielded a log higher and more reproducible sequencing library compared with that obtained using the commonly used commercial kit. The sequencing library prepared from HiTE-extracted FFPE-DNA had longer inserts and produced reads that evenly covered the reference genome. Successful application of HiTE-extracted FFPE-DNA for whole-genome and targeted gene panel sequencing indicates its practical usability.